2021
DOI: 10.4236/aim.2021.115018
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Assessment and Antibiotic Susceptibility Profile of Bacteria Recovered from <i>Clarias gariepinus</i> Selected from Various Fish Farms in Anambra North Senatorial Zones in Anambra State, Nigeria

Abstract: Fishes are cheap sources of protein and are commonly reared in artificial pond in Nigeria. Bacterial infested fishes have been a serious public health concern. This study was aimed at isolating and identifying bacteria associated with the internal organs (gills, liver, guts) of Clarias gariepinus (African Catfish) in fish ponds in Anambra North Senatorial zones in Anambra State, Nigeria, and to determine the seasonal bacterial load of the organs and antibiotic susceptibility profile of the isolates to conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…The results from the earthen pond (Cultured fish habitat) and New Calabar River (Wild environment), the bacterial load reported in the gills (Tables 1) was high in both Clarias gariepinus and A. heudelotii. This finding agrees with the findings of Ogbukagu et al [39], who recovered more bacteria in the gills of the catfish. Our study also reechoed the same concern expressed by Nwankwo & Akani [9], that the presence of these organisms could constitute a public health risk and calls for adequate preventive measures.…”
Section: Discussionsupporting
confidence: 93%
“…The results from the earthen pond (Cultured fish habitat) and New Calabar River (Wild environment), the bacterial load reported in the gills (Tables 1) was high in both Clarias gariepinus and A. heudelotii. This finding agrees with the findings of Ogbukagu et al [39], who recovered more bacteria in the gills of the catfish. Our study also reechoed the same concern expressed by Nwankwo & Akani [9], that the presence of these organisms could constitute a public health risk and calls for adequate preventive measures.…”
Section: Discussionsupporting
confidence: 93%
“…This observation correlates well with the diarrhoea prevalence of 8.7% of the total number of outpatients recorded in 2006. Transportation of fish from contaminated farms, the packaging of fish in dirty baskets and plastic basins, and the display of fish on dirty nylon sheets for buyers 20 meters from the fish farms could also enhance post-harvest contamination of the fish by the fish farmers [56,57,58]. In this study, it was observed that 14.29% of microbes were found on the skin of fish at Emohua LGA, 23.81% on fish skin at Eleme, 28.57% on fish skin at Ikwerre, 14 LGA while at Emuoha, Eleme and Port Harcourt city, 18, 7 and 5% each formed the bacteria load in the gut were as Ikwerre and Obio/Akpor respectively formed 31.25% and 12.50% of microbes.…”
Section: Discussionmentioning
confidence: 99%